Psychosocial support and cognitive deficits in adults with schizophrenia. (August 2014) - Dalagdi, Aikaterini; Arvaniti, Aikaterini; Papatriantafyllou, John; Xenitidis, Kiriakos; Samakouri, Maria; Livaditis, Miltos
Background: In recent decades there has been an increasing interest in cognitive deficits in schizophrenia. However, only a few studies have examined the impact of psychosocial support on the prevention of cognitive deterioration in patients who suffer from schizophrenia. Aim: The aims of the present study are: (1) to confirm the presence of cognitive deficits among patients with schizophrenia; (2) to explore any correlations between such deficits and a range of clinical and/or demographic characteristics of the patients; and (3) to investigate any association between cognitive deficits and psychosocial support. Method: A total of 118 patients with schizophrenia (the patient group) and 102 healthy volunteers (the control group) had a cognitive assessment using a battery of neuropsychological tests. The patients were allocated to one of the following groups: (1) patients under routine outpatient follow-up; or (2) patients receiving or having recently received intensive psychosocial support, in addition to follow-up. This included daily participation in vocational and recreational activities provided by dedicated mental health day centers. The findings of the neuropsychological testing of individuals in all groups were compared, after controlling for clinical or demographic factors. Results: The scores in the neuropsychological tests were lower overall in the patients group compared to healthy volunteers. Within the patients group, those receiving/having received psychosocial support had higher scores compared to those on routine follow-up alone. There were no significant differences between patients currently receiving psychosocial support and those having received it in the past. Lower education, age and illness duration (but not severity of positive or negative symptoms) were factors associated with lower test scores. Conclusions: The study provides some evidence that psychosocial support may be beneficial for the cognitive functioning of patients with schizophrenia and this benefit may be a lasting one.